Triniteit, mannelijkheid en vrouwelijkheid – Een kritische analyse en zoektocht naar een verantwoordelijke methode - Leene, Alida Maria Jantina (Stellenbosch Theological Journal, 2016)
Trinity, masculinity and the feminine – a critical analysis in search of a responsible methodology Regarding the relationship between the Trinity and gender, theologians differ radically. This article first show how the Trinity is seen as a model for gender relationships from an immanent and economic point of view. Thereafter the critique of projection is discussed. In searching for a theological responsable method, the image of God is bought in as a key for understanding the creation of male and female. A Trinitarian and relational perspective on the image of God is helpfull in focussing on the relationship with God, rather than the relations in God.